Keats et de Kooning : Pour un romantisme expressionniste abstrait ou la mise en image de l’épitaphe - Caroline Bertonèche (Revue LISA)
The article explores the comparative dialectic between John Keats’s choice of a visual epitaph, theatrically staged as a fluid, evanescent metaphor of poetic identity in relation to Romantic writing, and Willem de Kooning’s late awareness and expressionist interpretation of it. The modernity of Keats’s epitaphic imagery seemed to have been an uncanny preamble to de Kooning’s gestural art or pictorial pantomimes on the themes of impermanence and forgetfulness, memory and death. Close in many other ways, despite chronological and geographical differences, the two inspired artists meet around their creative intermingling of the picturesque and the poetic: the rhythmic liquidity, the verse schemes, the chiaroscuros, the ‘dripping’ technique, the ‘erasures’, the fading colours… Keats’s strangely melancholic but also deeply ironic and contrasted lyricism meets de Kooning’s mixed style of painting, torn as it is between the realms of tradition and novelty, of figurative and abstract art. A writer and a reader, an indolent poet and an ‘action painter’, they are, above all, or aspire to be, especially with regard to this mysterious conception and meaningful depiction of an epitaph, immortal artists as well as enlightened visionaries.